PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA TENAGA KEPENDIDIKAN DI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO DENGAN VARIABEL INTERVENING KEPUASAN KERJA - Lindrawati, Lindrawati; Hamdun, Edy Kusnadi; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2023)
This human resources research aims to determine the effect of motivation and discipline of education personnel on the performance of education personnel with the intervening variable, namely the achievement of job satisfaction for education personnel at Abdurachman Saleh University Situbondo. This research was studied by calculating the system / structural equation model Partial Least Square (PLS). from the calculation of the results of the hypothesis test results, it has a direct effect using the Smart PLS 3.0 application. the results of research testing show that motivation and work discipline have a positive effect on the performance and satisfaction of education personnel as an intervening variable.